INDONESIAN PORTRAYED IN ENGLISH GENRE TEXTS: A STUDENT’S WORKSHEET ANALYSIS - Lilik Tri Mulyani (Universitas Ahmad Dahlan)
Indonesia, from Sabang to Merauke, has thousands of archipelagos which lead it to have cultural diversity. Recognizing its huge diversity is important to build the national unity. One of the ways is through education. In fact, National Examination is stated as the benchmark to the national educational equality. This paper aimed to analyze the Indonesian local wisdom written in the English genre text in the student’s national examination preparation. It deals with the brief description about the content of the student’s worksheet, titled Prediksi UN SMP Bahasa Inggris published by Graha Pustaka Jakarta Indonesia. This is a descriptive research which the student’s worksheet is as the main data. It becomes one of students’ compulsory books for one of Junior High school in Jombang, East Java in facing National Examination. The result shows that there are 5 text types provided; Descriptive, Procedure, Narrative, Recount and Report. From the text types above, there are 18 % texts which describe/ tell about the how Indonesia is described through the description (Descriptive and Recount text ), and folklore (Narrative). The descriptions will make students more recognize and love Indonesia through its diversity (e.g. Monumen Nasional, Ari’s Grandmother, etc, and the story can be learnt its moral value (e.g. the history of Cenderawasih, etc) to be applied in daily life. Finally, the researcher hopes that this research gives big contribution to all the readers particularly for the publishers to select the text with the Indonesian local wisdom so that the students will have high awareness and love to their nation.